Analytical Hierarchy Process Approach in Determining Priority of Ecotourism Land to Support Community Economic Independence in Baranti District - Atika Izzaty; Suharman Hamzah; Muhammad Akbar Walenna; Farid Sitepu; Raden Aisyah Nur; Herlina Anwar (Faculty of Engineering UNHAS, 2026)
Integrating environmental conservation, community empowerment, and local economic growth into ecotourism land allocation is essential for sustainable development. The objective of this community service activity is to implement the Analytical Hierarchy Process (AHP) approach to determine the level of ecotourism land suitability in Baranti District, Sidenreng Rappang Regency, South Sulawesi, thereby enhancing the community’s capacity to understand and apply data‑driven decision‑making. A participatory approach was applied by involving the community in determining the criteria and location priorities. The respondents for the pre‑test and post‑test were members of farmer groups, totaling 25 individuals. The evaluation conducted through the pre‑test and post‑test shows that 22.40% of participants experienced an improvement in understanding after attending the socialization and the application of automation‑based methods in decision‑making. The AHP analysis results indicate that the slope gradient criterion has the highest weight at 0.35, followed by road access at 0.25 in determining land suitability. Sipodeceng Village, located in Baranti District, was identified as the priority location with a high suitability level based on geographic criteria. Areas with a slope gradient of 3–15% are the most suitable for ecotourism development. The determination of ecotourism land priorities serves as a basis for decision‑making in the development of agricultural ecotourism areas, thereby supporting the enhancement of economic independence among communities in Baranti District.